2023
DOI: 10.1111/1477-8947.12309
|View full text |Cite
|
Sign up to set email alerts
|

Climate resilience, yield and geographical suitability of sweet potato under the changing climate: A review

Abstract: Sweet potato is one of the important tropical tuber crops across the world. This review analyzes the studies on the climate resilience of sweet potato to various environmental parameters, the impact of climate change on its yield, and geographical suitability to exploit more about this crop and find out the knowledge gap in its existing research. Drought tolerance studies indicate the suitability of sweet potato in drought‐prone areas in terms of their survival rate, and their leaves can tolerate up to a wilti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Sweet potatoes have an observed salt tolerance of 11 dS m −1 , which is higher than that of other important crops. Compared to other crops, sweet potatoes have a better ozone tolerance (59 ppb) (Pushpalatha & Gangadharan, 2023). Temperature did not alter the overall number of storage roots produced when temperature treatments were applied after the storage roots were created, but it did have a substantial impact on the size and quality of the storage roots.…”
Section: Resultsmentioning
confidence: 99%
“…Sweet potatoes have an observed salt tolerance of 11 dS m −1 , which is higher than that of other important crops. Compared to other crops, sweet potatoes have a better ozone tolerance (59 ppb) (Pushpalatha & Gangadharan, 2023). Temperature did not alter the overall number of storage roots produced when temperature treatments were applied after the storage roots were created, but it did have a substantial impact on the size and quality of the storage roots.…”
Section: Resultsmentioning
confidence: 99%
“…The water requirement studies in sweet potato (Ipomoea batatas) also revealed increase in tuber tuber yield with sufficient moisture in soil. Suitability of sweet potato in drought-prone areas in terms of their survival rate was reported by various drought tolerance studies and their leaves can tolerate up to a wilting point of −1.3 MPa [22]. According to Laurie et al [23], drought had a harmful impact on the growth of the sweet potato plants and drought-induced growth retardation has a significant impact on its yield.…”
Section: Sweet Potatomentioning
confidence: 99%